The Role of Autophagy in Inflammatory Bowel Disease - Shao, Bo-Zong; Yao, Yi; Zhai, Jun-Shan; Zhu, Jian-Hua; Li, Jin-Ping; Wu, Kai (Frontiers in Physiology, 2021)
Inflammatory bowel disease (IBD) is an idiopathic intestinal inflammatory disease, including ulcerative colitis (UC) and Crohn’s disease (CD). The abnormality of inflammatory and immune responses in the intestine contribute to the pathogenesis and progression of IBD. Autophagy is a vital catabolic process in cells. Recent studies report that autophagy is highly involved in various kinds of diseases, especially inflammation-related diseases, such as IBD. In this review, the biological characteristics of autophagy and its role in IBD will be described and discussed based on recent literature. In addition, several therapies for IBD through modulating the inflammasome and intestinal microbiota taking advantage of autophagy regulation will be introduced. We aim to bring new insight in the exploration of mechanisms for IBD and development of novel therapeutic strategies against IBD.